Model Predictive Control for Linear Complementarity and Extended Linear Complementarity Systems - Riyanto, Bambang; Hakim, Ibrahin (ITB Journal Publisher, LPPM ITB, 2005)
Â In this paper, we propose model predictive control method for linear complementarity and extended linear complementarity systems by formulating optimization along prediction horizon as mixed integer quadratic program. Such systems contain interaction between continuous dynamics and discrete event systems, and therefore, can be categorized as hybrid systems. As linear complementarity and extended linear complementarity systems finds applications in different research areas, such as impact mechanical systems, traffic control and process control, this work will contribute to the development of control design method for those areas as well, as shown by three given examples.